Inhibition of Raf Kinase in the Treatment of Acute Myeloid Leukemia - Crump, M. (Current Pharmaceutical Design, 2002)
Adult acute myeloid leukemia (AML) and the myelodysplastic syndromes (MDS) remain a formidable therapeutic challenge. Although 30-40% of young adults with AML may have prolonged remissions, following either intensive chemotherapy or bone marrow transplantation, the remainder relapse and ultimately die of their disease. Older adults, or those with leukemia following an antecedent hematologic disorder such as MDS, experience only brief remissions with modern chemotherapy, and in this population the rate of long-term disease-free survival is less than 10%. Treatment of MDS consists mainly of supportive care with antibiotics and transfusion therapy, and only a small minority of patients are cured with allogeneic stem cell transplantation. As the biology of the acute leukemias and MDS has unfolded, new potential targets for arresting malignant cell growth and restoring normal hematopoiesis have been identified. This article will discuss the relevance of the ras-raf signaling pathway in the pathogenesis of myeloid leukemia, and describes some early results in the use of novel small molecule inhibitors of farnysltransferase and raf protein kinase in leukemia therapy.
Keywords: raf kinase